The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1097/01.prs.0000060995.99380.de
|View full text |Cite
|
Sign up to set email alerts
|

Morphometry of the Adult Human Earlobe: A Study of 547 Subjects and Clinical Application

Abstract: The purpose of this study was to define the factors that influence earlobe length and to establish a standard for adult earlobe length by sex and age. The study sample consisted of 547 adult subjects older than 20 years of age. A randomized, prospective design was used. Patients with malignancies, previous surgery or trauma to the earlobe, or congenital earlobe anomalies were excluded. The following variables were studied: sex; age; ethnic origin; skin complexion; height, weight, and body mass index; and pierc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0
5

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(72 citation statements)
references
References 21 publications
3
61
0
5
Order By: Relevance
“…In the current study, mean scores of EW for females were 3.06 cm and 2.97 cm on right and left sides respectively and those for males were 3.44 cm and 3.25 cm on right and left sides respectively, the difference being statistically significant in both sexes. Aging in human is characterized by elongation or ptosis of ear lobules which is a result of gravity and depletion of elastic fibres [16] and is worsen by an extra weight of earrings in females [17]. The mean LH was more on left ear (1.69 cm) than right (1.67 cm) in both males and females and showed no significant difference [15].…”
Section: Resultsmentioning
confidence: 99%
“…In the current study, mean scores of EW for females were 3.06 cm and 2.97 cm on right and left sides respectively and those for males were 3.44 cm and 3.25 cm on right and left sides respectively, the difference being statistically significant in both sexes. Aging in human is characterized by elongation or ptosis of ear lobules which is a result of gravity and depletion of elastic fibres [16] and is worsen by an extra weight of earrings in females [17]. The mean LH was more on left ear (1.69 cm) than right (1.67 cm) in both males and females and showed no significant difference [15].…”
Section: Resultsmentioning
confidence: 99%
“…The lengths of both auricles were always larger in males than females of corresponding age in a study from Italy (Ferrario et al, 1999). In an Israeli population, earlobe length was found larger in males than females for both ears and the differences were statistically significant (Azaria et al, 2003). The average values of auricle length, earlobe length and width of right and left auricles were determined in a Rhode Island population and reported as auricle measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Sexual dimorphism is seen in the auricular linear dimensions with higher values in males. Brucker et al [5] observed an average LH to be 1.88cm and according to a study done by Bozkir et al [2] LH was 1.8 cm in young men and 1.7 cm in young women. Mc Kinney et al [15] obtained data from 100 volunteers and found a mean LH of 1.8 cm.…”
Section: Methodsmentioning
confidence: 99%
“…An acquired deformity that develops with aging may include elongation or ptosis of the ear lobe. This condition has been attributed to the loss of elastic fibres and gravitational forces [5]. The height of the lobe covers approximately 25% of the length of the ear and varies between 1.5 -2 cm.…”
Section: Introductionmentioning
confidence: 99%